From paradigms to policies: Economic models in the EU's fiscal regulation framework - Jakob Kapeller; Philipp Heimberger; Jakob Huber (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2017)
This paper analyzes the impact of economic ideas on political processes and decision-making by focusing on the role and impact of the European Commission's "potential output model". The potential output model represents a core pillar in European fiscal policy coordination, that is, in executing the Stability and Growth Pact as it provides estimates for the "structural deficits" used to evaluate member states' fiscal effort. Our analysis builds on a historical and technical contextualization of the model's origin and content, which is complemented by a case study database including policy documents, public speeches and interviews with high-level practitioners in the respective field. We document that the potential output model has a significant imprint on political processes and outcomes: first, it manufactures legitimacy in contested policy-area. Second, it maps paradigmatic priors into specific and executable programs, thereby reducing the general scope in debates on economic policy. Finally, the model's main concepts and routines are embedded in a corresponding narrative, which is used to communicate the model's implications to a broader audience.
Keywords: 330